The China plant trait database version 2 - Han Wang; Sandy P. Harrison; Meng Li; I. Colin Prentice; Shengchao Qiao; Runxi Wang; Huiying Xu; Giulia Mengoli; Yunke Peng; Yanzheng Yang (Scientific Data, 2022)
Measurement(s) plant functional traits Technology Type(s) plant functional traits Sample Characteristic - Organism Plants Sample Characteristic - Location China